Spontaneous Adrenal Hemorrhage in Pregnancy: A Case Series [23H]. (May 2016) - Gupta, Ankita; Minhas, Ruby; Quant, Hayley S.
Abstract : INTRODUCTION: Abdominal pain during pregnancy has a broad differential diagnosis which includes spontaneous adrenal hemorrhage (SAH). A high index of suspicion is necessary to diagnose SAH as most patients present with nonspecific symptoms including pain, fever and hypotension. Rarely, patients can develop retroperitoneal bleeding and present with hemodynamic instability. METHODS: We present two cases of symptomatic SAH in the third trimester. Patient 1 was a 35 year old nullipara who presented at 36 weeks of gestation with left flank pain. Patient 2 was a 27 year old multipara at 38 weeks who presented with left upper quadrant pain. Initial suspicion was for renal pathology in both cases and diagnosis of SAH was ultimately made by CT scan. Both were managed with pain control, serial hemoglobin assessments and abdominal exams and resulted in uncomplicated vaginal deliveries. Interval CT scan in patient 2 demonstrated a complete resolution of pathology. RESULTS: If unrecognized, adrenal hemorrhage can lead to adrenal crisis, shock and theoretically death for both mother and fetus. While the initial imaging study in pregnancy is ultrasound, MRI or CT scan is needed for confirmation. Recommended laboratory evaluations include serial hemoglobin measurements as well as assessment of adrenal function. Scant literature is available on optimal mode of delivery but in a stable patient, vaginal delivery can be safely undertaken. CONCLUSION: SAH, although rare, is an important consideration when evaluating abdominal and flank pain in pregnancy. Management options vary from conservative management to surgical intervention depending on the stability of the patient.